2015
DOI: 10.3389/fimmu.2015.00380
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to Automated Flow Cytometry Gating Tools and Their Implementation

Abstract: Current flow cytometry (FCM) reagents and instrumentation allow for the measurement of an unprecedented number of parameters for any given cell within a homogenous or heterogeneous population. While this provides a great deal of power for hypothesis testing, it also generates a vast amount of data, which is typically analyzed manually through a processing called “gating.” For large experiments, such as high-content screens, in which many parameters are measured, the time required for manual analysis as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 33 publications
1
64
0
1
Order By: Relevance
“…The authors suggested steps that must be followed to reduce the sources of error in FCM results. The importance of standardizing an appropriate gating strategy and multiple data analysis methods are highlighted in detail in one previous study (56).…”
Section: Flow Cytometric Analysis Of Endothelial Progenitor Cells In mentioning
confidence: 99%
“…The authors suggested steps that must be followed to reduce the sources of error in FCM results. The importance of standardizing an appropriate gating strategy and multiple data analysis methods are highlighted in detail in one previous study (56).…”
Section: Flow Cytometric Analysis Of Endothelial Progenitor Cells In mentioning
confidence: 99%
“…It would be interesting to compare our automated software with other computational methods (45,46). The use of antibody pools allows the identification of PC as efficiently as the reference method by using the same number of markers (CD19, CD27, CD56, CD117, and CD200), while decreasing the number of fluorophores.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, results obtained with manual gating rely on a subjective analysis and this can generate inter-and intra-analyst differences. It would be interesting to compare our automated software with other computational methods (45,46). Compared to the standard recommended 8-color panel using two tubes from the Euroflow consortium (12), the antibody pools of the smart panel could decrease the number of fluorophores and lasers needed with the advantage of the automated PC detection and analysis and similar specificity and sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate adjustment of biexponential scaling is important to clearly and completely visualize all populations, particularly for intracellular cytokine staining. For more complex examination of S1P signalling, computational assistance analysis could be an alternative only after critical assessment and verification [16,17].…”
Section: Notesmentioning
confidence: 99%